2021
DOI: 10.3389/fnins.2021.599593
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Cognitive Decline and the Olfactory Identification Deficit Are Associated to Increased Level of Depression

Abstract: PurposePrevious studies reported a correlation between olfactory function and depression. However, in literature, no data are available for the correlation between depression and all other factors such as age, sex, olfactory, gustatory, and cognitive function in healthy subjects taken together. The aim of this study was to provide a systematic account regarding the association between those variables in a non-clinical population.MethodsTwo hundred and seventy-three participants were recruited with an age range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 57 publications
1
18
0
Order By: Relevance
“…Moreover, our results confirmed that OI was correlated to age, sex, and cognitive reserve index (CRI). In line to many previous studies [4,5,48,57] we found a significant reduction in olfactory performance in relation to age increasing. Several theories were proposed for this age-related decrease in olfactory function, which may be related to a reduced number of olfactory receptor neurons, along with a decreased number of fibers in the olfactory bulb [28,58], changes at a cortical level, changes in the number and in the width of the holes on the cribriform plate, or changes in the mucus composition [57].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Moreover, our results confirmed that OI was correlated to age, sex, and cognitive reserve index (CRI). In line to many previous studies [4,5,48,57] we found a significant reduction in olfactory performance in relation to age increasing. Several theories were proposed for this age-related decrease in olfactory function, which may be related to a reduced number of olfactory receptor neurons, along with a decreased number of fibers in the olfactory bulb [28,58], changes at a cortical level, changes in the number and in the width of the holes on the cribriform plate, or changes in the mucus composition [57].…”
Section: Discussionsupporting
confidence: 93%
“…A sample size calculation was performed to assess the required minimum number of subjects to be enrolled in the study. Based on previous studies using similar protocols [5,21,47,48], a minimum number of about 450 total subjects was considered adequate to detect investigated differences. In fact, a power calculation, considering a critical effect size f = 0.20-0.25 (medium effect), with 95% power and a 5% significance level in a standard two-way ANOVA, suggested a minimal required number of about 450 total subjects, and a power calculation considering a critical effect size f 2 = 0.10-0.15 (medium effect), with 95% power, and a 5% significance level for each investigated factor in a multiple linear regression model, suggested a required minimum number of about 200 total subjects.…”
Section: Discussionmentioning
confidence: 99%
“…The amygdala and orbitofrontal cortex are not only olfactory processing regions but also emotion and cognition regulatory structures, thereby potentially drawing connections between olfactory function, emotion regulation, and cognitive control (Heimer et al, 2007;Kohli et al, 2016). Studies on patients with psychiatric (e.g., schizophrenia and depression) and neurodegenerative (e.g., Parkinson's disease and Alzheimer's disease) disorders have discovered that hyposmia often accompanies emotional symptoms (Martzke et al, 1997;Croy et al, 2014;Kohli et al, 2016;Croy and Hummel, 2017) and cognitive decline (Masala et al, 2018;Sanna et al, 2021). Although olfactory identification and recognition performances were reported to be comparable between patients with mild or moderate depressive disorder and healthy controls (Zucco and Bollini, 2011), decreased odor discrimination ability was associated with a more impulsive tendency even within the non-clinical population (Herman et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Beyond the risks that the smell loss may entail for older people, moreover the consequent reduction in quality of life, the olfactory dysfunction may be an important early indicator of ND such as Parkinson’s and Alzheimer’s ( Djordjevic et al, 2008 ; Haehner et al, 2013 ; Knudsen et al, 2015 ; Doty, 2017 ; Marin et al, 2018 ; Kondo et al, 2020 ), as well as COVID-19 ( Moein et al, 2020 ; Sedaghat et al, 2020 ). In addition, olfactory system dysfunctions have been found in other neurological disorders such us schizophrenia, or depression ( Sanna et al, 2021 ) ultimately related to alterations of the immune system, suggesting that olfactory system abnormalities may be also associated with the immune system (reviewed in Strous and Shoenfeld, 2006 ). During the last years, olfactory proteomics has been postulated as a powerful approach to characterize global proteome dynamics in order to unravel the modulation of cell-signaling networks during odor processing ( Lachén-Montes et al, 2016 ), as well as during the neurodegenerative process ( Lachén-Montes et al, 2017 , 2019a , b , 2020a ).…”
Section: Introductionmentioning
confidence: 99%